PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI DI PT ANGSA KUSUMA INDAH DENPASAR - Hartawan, Anak Agung Bagus Aris; Sriathi, Anak Agung Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023DO - 10.24843/EEB.2023.v12.i02.p12, 2023)
That Performance is basically the result of an employee's work. The success or failure of an employee is influenced by the level of employee performance individually or in groups. The purpose of this study was to analyze the effect of job satisfaction on employee performance with organizational commitment as a mediating variable at PT. Angsa Kusuma Indah. This research was conducted at PT. Angsa Kusuma Indah, with the samples of 48 employees using a saturated sampling technique. The Data collection was carried out using observation and interviews, with the research instrument used was a questionnaire. The collected data was then analyzed using variant-based SEM or PLS. The results of the study found that job satisfaction has a positive and significant effect of employee performance at PT. Angsa Kusuma Indah. The Job satisfaction has a positive and significant effect on organizational commitment at PT. Angsa Kusuma Indah. Organizational commitment has a positive and significant effect on employee performance at PT.Angsa Kusuma Indah. In this way, the organizational commitment partially mediates the effect of job satisfaction on employee performance at PT. Angsa Kusuma Indah .